EVALUASI KETERSEDIAAN KOLEKSI DI PERPUSTAKAAN SEKRETARIAT DAERAH PROVINSI KALIMANTAN BARAT - Ari, Ari; Madeten, Sisilya Saman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to evaluate the availability of collection at the Regional library of West Kalimantan. Research result showing the books collection that available at library have 6.773 books with 732.090 copies. Type and number collections that available: 251 title with 753 copies of general works books, 359 title with 1.185 copies of philosophy and psychology books, 587 title with 1.174 copies of religion books, 2.460 title with 7.380 copies of social science books, 131 title with 524 copies of language books, 107 title with 428 copies science books, 982 title with 2.046 copies of applied science books, 116 title with 464 copies of art sport books, 365 title with 730 copies of literature books, 574 title with 1.156 copies of history and geography books, 88 volume with 696.960 copies of Akcaya daily newspaper, 48 volume with 17.280 copies of Pontianak Post newspaper. Can be concluded the highest numbers of books are Social Science at class 300 which the total are 2.460 title with 7.380 copies. Keyword: Collection Availability, Evaluation, Special Library